INSTITUTIONAL AND LEGAL MECHANISMS FOR THE PUBLIC-PRIVATE PARTNERSHIP DEVELOPMENT IN THE VOCATIONAL EDUCATION FIELD: THE SERBIA EXPERIENCE (Innovative professional education, 2023)
The relevance of the foreign experience study in the PPP implementation in the vocational education field is outlined. The most important organizational and institutional components of the education sector in the Serbia Republic are highlighted with the shortcomings and measures to overcome them. The similarities and differences signs in approaches to the educational industry as a whole and to the PPP introduction in the vocational education system in the Serbia Republic and Ukraine are analyzed. Based on the analysis, the expediency of using the Serbia Republic's experience in the scientific study of institutional and legal mechanisms for improving vocational education in Ukraine is approved.
Keywords: public-private partnership, vocational education, Serbia Republic, Ukraine